1994
DOI: 10.1159/000126782
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin B Receptor Gene Expression in Hypothalamic Neurosecretory Neurons after Experimental Manipulations

Abstract: Magnocellular neurons of the supraoptic (SON) and paraventricular (PVN) nuclei projecting to the neurohypophysis produce, in addition to the classical hormones vasopressin and oxytocin, a large number of other peptides, one of which is cholecystokinin (CCK). Binding sites for CCK have been identified in the posterior pituitary. Recently the cDNAs for CCKA and CCKB receptors were isolated and characterized, and CCKA and CCKB receptor mRNAs were localized in the SON an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The expression of peptides and their receptors shows a high degree of plasticity as reported in the brain, including magnocellular hypothalamic neurons (Hinks et al, 1995;Larsen et al, 1992aLarsen et al, ,b, 1993Meister et al, 1990Meister et al, , 1994Villar et al, 1990) and in the periphery . The present results clearly demonstrate that GAL-R1-Rs in the magnocellular hypothalamic neurons can also be regulated by various types of manipulations (Fig.…”
Section: Regulation and Functional Role Of Gal-r1 Receptors And Galaninmentioning
confidence: 88%
“…The expression of peptides and their receptors shows a high degree of plasticity as reported in the brain, including magnocellular hypothalamic neurons (Hinks et al, 1995;Larsen et al, 1992aLarsen et al, ,b, 1993Meister et al, 1990Meister et al, , 1994Villar et al, 1990) and in the periphery . The present results clearly demonstrate that GAL-R1-Rs in the magnocellular hypothalamic neurons can also be regulated by various types of manipulations (Fig.…”
Section: Regulation and Functional Role Of Gal-r1 Receptors And Galaninmentioning
confidence: 88%
“…Further, in vitro autoradiography proved the presence of CCK receptors in the PVN and studies using quantitative in situ hybridization unveiled nutrient dependent changes in the synthesis of the CCK-B receptor in the PVN [17, 18]. These neuroanatomical observations and the lack of effect of the CCK-A receptor antagonist on colonic transit when microinfused into the PVN in the present study indicate, that CCK released from terminal endings of neurons in the PVN which subsequently acts on CCK-B receptors within this brain area is involved in the CNS regulation of colonic motility.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence has been provided that CCK is released in the PVN in response to a meal, and that CCK in the periphery may also induce release of this peptide in hypothalamic regions including the PVN [31]. Further, the PVN is well established to play a role in CNS regulation of GI motility and feeding, and nutrient dependent changes in the synthesis of the CCK-B but not the CCK-A receptor have been demonstrated in the PVN [11, 14, 18]. Also, endogenous CCK causes satiety by an agonist action on CCK-B receptors in the brain [28], and it has been shown that activation of hypothalamic but not brainstem neurons induced by CCK administered systemically could be attenuated by central application of a CCK-B receptor antagonist [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hypothalamus, both CCK‐A and CCK‐B receptor gene expression has been detected in the paraventricular nucleus (PVN) (Meister et al ., 1994). In addition, intraperitoneal administration of CCK‐8 activates catecholaminergic neurons in the caudal medulla projecting to the PVN (Rinaman et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%